2008
DOI: 10.1111/j.1365-2222.2008.02990.x
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H1‐receptor antagonists inhibit nuclear factor‐kappaB and activator protein‐1 activities via H1‐receptor‐dependent and ‐independent mechanisms

Abstract: Background Histamine H1-receptor antagonists are used to relieve the symptoms of an immediate allergic reaction. They have additional anti-inflammatory effects that could result from an inhibition of the transcription factors activator protein-1 (AP-1) and nuclear factorkappa B (NF-kB). The implication of the H1-receptor in these effects is controversial. Diphenhydramine is a first-generation H1-receptor antagonist while mizolastine and desloratadine are second-generation compounds. Mizolastine is also an inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 48 publications
(57 reference statements)
1
23
0
Order By: Relevance
“…Roumestan et al have shown that antihistamines inhibit NF-kappaB through both H1 receptor-dependent and independent mechanisms. 36 This profile does not replicate when compared to the equivalent group (Respiratory Agent: Histamine Antagonist) from the dataset presented by Polymeropoulos et al, though a similar trend is seen. The average number of probes in common is four and one respectively, for the up-and downexpressed signatures (p = 1.13E−03 and p = 3.60E−01).…”
Section: Antihistamine Group (R06a)supporting
confidence: 51%
“…Roumestan et al have shown that antihistamines inhibit NF-kappaB through both H1 receptor-dependent and independent mechanisms. 36 This profile does not replicate when compared to the equivalent group (Respiratory Agent: Histamine Antagonist) from the dataset presented by Polymeropoulos et al, though a similar trend is seen. The average number of probes in common is four and one respectively, for the up-and downexpressed signatures (p = 1.13E−03 and p = 3.60E−01).…”
Section: Antihistamine Group (R06a)supporting
confidence: 51%
“…Histamine by its action on H 1 receptors has been shown to activate NF-ĸB, an important transcription factor that binds with promoter/enhancer regions of genes regulating production of a number of pro-inflammatory cytokines and adhesion molecules [42]. Antihistamines down-regulate activation of NF-ĸB to inhibit inflammatory cell accumulation and activation [43]. Cetirizine and azelastine have been shown to down-regulate NF-ĸB expression in parallel with inhibition of generation of the cytokines, IL-1β, IL-6, IL-8, TNF-α and GM-CSF [44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…Although no mechanistic explanation was described, suppression of NF-κB by Kujin was reported [29,30]. Activation of NF-κB by histamine through H1R was also reported [19]. We have not examined the effect of Kujin extract on NF-κB activation in the nasal mucosa from TDIsensitized rats.…”
Section: Discussionmentioning
confidence: 87%
“…Histamine was shown to activate NF-κB through H1R [16][17][18]. Over expression of H1R by histamine led to a significant induction of NF-κB activities and this activity was inhibited by H 1 -antihistamines [19]. Recent study demonstrated the contribution of FAT 10 on NF-κB activation and subsequent expression of NF-κB-regulated genes [20].…”
Section: Introductionmentioning
confidence: 97%